Intravenous Lipid Infusion Induces Endoplasmic Reticulum Stress in Endothelial Cells and Blood Mononuclear Cells of Healthy Adults. Issue 1 (January 2016) - Tampakakis, Emmanouil; Tabit, Corey E.; Holbrook, Monika; Linder, Erika A.; Berk, Brittany D.; Frame, Alissa A.; Bretón‐Romero, Rosa; Fetterman, Jessica L.; Gokce, Noyan; Vita, Joseph A.; Hamburg, Naomi M.
Abstract : Background: Endoplasmic reticulum (ER) stress and the subsequent unfolded protein response may initially be protective, but when prolonged, have been implicated in atherogenesis in diabetic conditions. Triglycerides and free fatty acids (FFAs) are elevated in patients with diabetes and may contribute to ER stress. We sought to evaluate the effect of acute FFA elevation on ER stress in endothelial and circulating white cells. Methods and Results: Twenty‐one healthy subjects were treated with intralipid (20%; 45 mL/h) plus heparin (12 U/kg/h) infusion for 5 hours. Along with increased triglyceride and FFA levels, intralipid/heparin infusion reduced the calf reactive hyperemic response without a change in conduit artery flow‐mediated dilation consistent with microvascular dysfunction. To investigate the short‐term effects of elevated triglycerides and FFA, we measured markers of ER stress in peripheral blood mononuclear cells (PBMCs) and vascular endothelial cells (VECs). In VECs, activating transcription factor 6 (ATF6) and phospho‐inositol requiring kinase 1 (pIRE1) proteins were elevated after infusion (both P <0.05). In PBMCs, ATF6 and spliced X‐box‐binding protein 1 (XBP‐1) gene expression increased by 2.0‐ and 2.5‐fold, respectively (both P <0.05), whereas CHOP and GADD34 decreased by ≈67% and 74%, respectively (both P <0.01). ATF6 and pIRE1 protein levels also increased (both P <0.05), and confocal microscopy revealed the nuclear localization of ATF6 after infusion, suggesting activation. Conclusions: Along with microvascular dysfunction, intralipid infusion induced an early protective ER stress response evidenced by activation of ATF6 and IRE1 in both leukocytes and endothelial cells. Our results suggest a potential link between metabolic disturbances and ER stress that may be relevant to vascular disease.